2021
DOI: 10.3390/antiox10081259
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Pigment Hemozoin Impairs GM-CSF Receptor Expression and Function by 4-Hydroxynonenal

Abstract: Malarial pigment hemozoin (HZ) generates the lipoperoxidation product 4-hydroxynonenal (4-HNE), which is known to cause dysregulation of the immune response in malaria. The inhibition of granulocyte macrophage colony-stimulating factor (GM-CSF)-dependent differentiation of dendritic cells (DC) by HZ and 4-HNE was previously described in vitro, and the GM-CSF receptor (GM-CSF R) was hypothesised to be a primary target of 4-HNE in monocytes. In this study, we show the functional impact of HZ on GM-CSF R in monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…Natural HZ was prepared as previously described (14, 15). Briefly, 12 h after schizogony of synchronized FCR3 parasite cultures, the supernatant was collected.…”
Section: Methodsmentioning
confidence: 99%
“…Natural HZ was prepared as previously described (14, 15). Briefly, 12 h after schizogony of synchronized FCR3 parasite cultures, the supernatant was collected.…”
Section: Methodsmentioning
confidence: 99%
“…That study showed involvement of CSF-2 in activation of granulocyte-macrophage hematopoiesis and resistance to P. chabaudi infection [ 83 ]. An explanation for the lack of differences in the levels of anemia in infected mice may stem from the action of the malarial pigment hemozoin, which impairs CSF-2 receptor expression and function [ 84 ]. However, Babesia spp.…”
Section: Phagocytosismentioning
confidence: 99%
“…93,111,112 In these immune cells, the overload of lipid oxidation products HETEs and 4-hydroxynonenal (4-HNE) due to HZ was observed 92,93,113 and their contribution to immune imbalance in malaria is described. [114][115][116] Impaired HETEs' metabolism by CYPs may contribute to immunologically active HETEs accumulation and immune imbalance (Figure 4). Thus, any damage to CYP enzymes could perturb a balanced immune response to malaria, and studies of specific CYPs affected in malaria is crucial.…”
Section: P450 and Host Immunity In Malariamentioning
confidence: 99%
“…In malaria, HZ is engulfed directly by phagocytes or is accumulated after phagocytosis of parasitized erythrocytes containing HZ 93,111,112 . In these immune cells, the overload of lipid oxidation products HETEs and 4‐hydroxynonenal (4‐HNE) due to HZ was observed 92,93,113 and their contribution to immune imbalance in malaria is described 114–116 . Impaired HETEs' metabolism by CYPs may contribute to immunologically active HETEs accumulation and immune imbalance (Figure 4).…”
Section: Malariamentioning
confidence: 99%